Preparation and Application of Egg Yolk Antibodies Against Chinese Sacbrood Virus Infection - Sun, Li; Li, Ming; Fei, Dongliang; Diao, Qingyun; Wang, Jian; Li, Liqin; Ma, Mingxiao (Frontiers in Microbiology, 2018)
Chinese sacbrood virus (CSBV) infects Apis cerana larvae, resulting in the inability of the larvae to pupate and their consequent death, which may pose a serious threat to entire colonies. As there is no effective medical treatment for CSBV infections, further studies are necessary. In this study, an effective treatment for CSBV is described, based on a specific immunoglobulin (IgY) from egg yolk against CSBV. The inactivated vaccine was produced by ultracentrifugation and formalin treatment, using CSBV purified from a natural outbreak. The specific IgY was produced by immunization of white leghorn hens with the vaccine. An enzyme-linked immunosorbent assay using purified CSBV as the coating antigen revealed that the anti-CSBV IgY titer began increasing in the egg yolk on the 14th day post-immunization, reaching a peak on day 42, and anti-CSBV IgY remained at a high level until day 91. IgY isolated from the combinations of egg yolk collected between days 42 – 91 was purified by PEG and ammonium sulfate precipitation. In three repeated protection experiments using A. cerana larvae inoculated with CSBV, the survival rate of larvae was more than 80%, and the titer of anti-CSBV IgY was more than 25 and 24 when the larvae were fed IgY 24 h after and before inoculation with CSBV, respectively. Therefore, 400 colonies infected with CSBV were treated by feeding or spraying sugar containing IgY solutions with an antibody titer of 25, and the cure rate was 95% – 100%. Three hundred susceptible colonies were protected by feeding or spraying the larvae with sugar containing IgY solutions with an antibody titer of 24, and the protection rate was 97%. The results clearly suggest that a specific IgY was obtained from hens immunized with an inactivated-CSBV vaccine, and this may be a novel method for controlling CSBV infection.